Solid-supported block copolymer membranes through interfacial adsorption of charged block copolymer vesicles - Rakhmatullina, Ekaterina (Langmuir : the ACS journal of surfaces and colloids, 2008)
The properties of amphiphilic block copolymer membranes can be tailored within a wide range of physical parameters. This makes them promising candidates for the development of new (bio)sensors based on solid-supported biomimetic membranes. Here we investigated the interfacial adsorption of polyelectrolyte vesicles on three different model substrates to find the optimum conditions for formation of planar membranes. The polymer vesicles were made from amphiphilic ABA triblock copolymers with short, positively charged poly(2,2-dimethylaminoethyl methacrylate) (PDMAEMA) end blocks and a hydrophobic poly( n-butyl methacrylate) (PBMA) middle block. We observed reorganization of the amphiphilic copolymer chains from vesicular structures into a 1.5+/-0.04 nm thick layer on the hydrophobic HOPG surface. However, this film starts disrupting and dewetting upon drying. In contrast, adsorption of the vesicles on the negatively charged SiO2 and mica substrates induced vesicle fusion and formation of planar, supported block copolymer films. This process seems to be controlled by the surface charge density of the substrate and concentration of the block copolymers in solution. The thickness of the copolymer membrane on mica was comparable to the thickness of phospholipid bilayers